An Evaluation of the Parenting Under Pressure (PuP) Programme at Coolmine - Ivers, Jo-Hanna; Barry, Joe (Coolmine Therapeutic Community, 2018)
Coolmine Therapeutic Community has opened its Parents under Pressure (PuP) programme to external scrutiny and evaluation. The PuP programme aims to improve family functioning and child outcomes by supporting parents who are, or have been, drug or alcohol dependent.Evaluations of the PuP programme have been carried out in other countries but never in Ireland. This is the first evaluation anywhere of the PuP programme in a residential setting.The current research aimed to investigate the feasibility and effectiveness of the PuP programme being delivered in a group setting in addition to one-to-one sessions at Ashleigh House. A combination of quantitative and qualitative research methods was employed.Twenty-three women took part in the research across three waves. 25 women enrolled in the PuP programme and twenty-three participated in the evaluation. It is noteworthy that no woman left the PuP programme. The two participants that did leave, left the treatment services (one was prematurely discharged and one self-discharged) rather than the programme.Moreover, a comparison of characteristics between participants retained showed no demographic or clinical differences. A series of demographic and clinical characteristics were gathered and analysed.Participants ranged in age from 22 years to 44 years of age. The average age were 34 years old. The women had complex needs beyond their drug use; 78% were homeless,73.9% had active social care involvement, 26%had criminal justice issues and 26% reported having a history of psychiatric problems. Twelve of the participants resided in Ashleigh House accompanied by their child. In all cases this was limited to a single child. All children that resided in Ashleigh House were under the age of five years. Of the twenty-three, 21 completed a number of pre and post validated outcome measures.Improvements were found in depression, stress and anxiety scores after the programme. Mindful parenting scores increased, and there was a real or perceived improvement in children's behaviour. At the end of the programme all women were drug and alcohol free.All twenty-three took part in the qualitative component of the study. Guilt was a dominant theme across the interview process. The principal expectation of the participants was to improve their relationships and access to their children. As the women progressed through the programme, they were visibly building belief in their abilities to parent. The group setting facilitated a sense of solidarity.Through the sharing of experiences, the women learned they were not alone. During the evaluation, PuP was being piloted for men at Coolmine Lodge. Thus, ten men took part in a pre and post programme focus groups and their experience is included. The men and women experienced challenges when participating in the programme.Regardless of whether or not they had acces sto their children, the benefits of participating in the PuP programme were apparent.External agencies such as social services and criminal justice were familiar with the PuP programme and participants received external validation and praise for their participation.All participants emphasised the importance of access during treatment. Most frequently two suggestions for change were put forth by participants; (1) including the children in the sessions and (2) adapting the content to include older adult children.The involvement of a programme coordinator and group facilitators is essential. PuP should be extended to all fathers. Teenage and young adult children of participants should be included in future programmes. A more extensive evaluation, with greater numbers and longer follow up, should be carried outwith particular emphasis on community outreach and the development of the programme to other non Therapeutic Community-based treatment settings.
Keywords: Parenting; Drug use; Alcohol dependence; Children; Family; Inclusive Society